2021
DOI: 10.1128/mbio.00455-21
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Modular Receptor-Binding Proteins ofKlebsiellaPhages Switches Their Capsule Serotype Specificity

Abstract: The high specificity of bacteriophages is driven by their receptor-binding proteins (RBPs). Many Klebsiella bacteriophages target the capsular exopolysaccharide as the receptor and encode RBPs with depolymerase activity. The modular structure of these RBPs with an N-terminal structural module to attach the RBP to the phage tail, and a C-terminal specificity module for exopolysaccharide degradation, supports horizontal transfer as a major evolutionary driver for Klebsiella phage RBPs. We mimicked this natural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 56 publications
(81 reference statements)
0
38
0
Order By: Relevance
“…Here, we have shown that there is a large untapped source of depolymerases for Acinetobacter capsule types, which could be used as anti-virulence or anti-biofilm agents against A. baumannii infections. Elucidating the tertiary structures of the additional depolymerases could provide a structural framework by which to produce enzymes with broader specificity, or allow the engineering of phages with altered host specificity, as peformed in Klebsiella phages [71].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that there is a large untapped source of depolymerases for Acinetobacter capsule types, which could be used as anti-virulence or anti-biofilm agents against A. baumannii infections. Elucidating the tertiary structures of the additional depolymerases could provide a structural framework by which to produce enzymes with broader specificity, or allow the engineering of phages with altered host specificity, as peformed in Klebsiella phages [71].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the success rate of cross-genus rebooting is higher than that of cross-order rebooting. Among the successfully rebooted phages, 77.8% do not belong to the T7 family, which is an improvement over prior research ( Ando et al., 2015 ; Latka et al., 2021 ). All 44 Pa phages were isolated against the same type strain, PAO1, but their rebooting outcome varied distinctly.…”
Section: Resultsmentioning
confidence: 62%
“…Representatives of strategy (1) are Bacteriophage Recombineering of Electroporated DNA (BRED)and BRED combined with CRISPR-Cas9 (CRISPY-BRED), which transform target DNA into native hosts by electroporation, accelerate DNA recombination and/or promote counterselection of recombinant phage genomes via plasmid-carried exogenous systems, and reboot engineered genomes in native hosts ( Marinelli et al., 2008 ; Wetzel et al., 2021 ). Representative of strategy (2) is the yeast platform, which achieved genome rebooting of T7-family phages in Escherichia coli 10G ( Ando et al., 2015 ; Latka et al., 2021 ). Representative of strategy (3) is the L-form bacteria platform, which successfully rebooted 9 Listeria phages, 2 Bacillus phages, and 2 Staphylococcus aureus phages in Listeria L-form cells ( Kilcher et al., 2018 ; Meile et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of other receptor-binding proteins additional to gp059 in vB_PmiS_PM-CJR may also explain the wider host range of the phage compared to the depolymerase. Although the narrow activity spectrum of phages is considered beneficial for clinical applications as it limits the effect of the phage on non-pathogenic constituents of the microbiota, protein engineering of the tail spike can be employed to expand its host range [ 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%